2009
DOI: 10.1007/s12562-009-0106-0
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of genetically modified soybean meal in Nile tilapia Oreochromis niloticus diets

Abstract: The utilization of genetically modified soybean meal (GM SBM) was compared with that of non-GM SBM in Nile tilapia. Four experimental diets were formulated to include either non-GM or GM SBM at 34 or 48%, respectively. These diets were fed to juvenile Nile tilapia (49.5 g average weight) for 12 weeks. The uptake of the cauliflower mosaic virus 35S promoter fragment of the GM SBM in fish muscle was examined at 8th and 12th week. After 12th week, fish were fed the non-GM SBM diets to determine the residual span … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Sissener et al [17] reported that fish fed diets containing either GM or nonGM SBM had similar nutritional and growth status. These results are also in agreement with previous studies reported in other species such as catfish [7], Atlantic salmon [8,9,18,19], rainbow trout [10], and Nile tilapia [11]. This similar growth performance is a result of similar feed composition using either GM or nonGM soybeans given to the experimental fish.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Sissener et al [17] reported that fish fed diets containing either GM or nonGM SBM had similar nutritional and growth status. These results are also in agreement with previous studies reported in other species such as catfish [7], Atlantic salmon [8,9,18,19], rainbow trout [10], and Nile tilapia [11]. This similar growth performance is a result of similar feed composition using either GM or nonGM soybeans given to the experimental fish.…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, the CaMV 35S promoter fragment was detected in the muscle of rainbow trout fed diets containing 15% GM SBM [8]. The CaMV 35S promoter fragment was also detected in the muscle of Nile tilapia fed diets containing 34 and 48% GM SBM [11]. In apparent contrast, CaMV 35S promoter fragment was not detected in the muscle of common carp fed 48% GM SBM diet.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations